Evaluation of Some Geotechnical Properties of Chosen Soils From Al- Massab Al-Aam channel Slopes (Middle Sector) of Iraq. - Alzubaydi, Jaffar H.; Alamar, Haider A.; Al saadi, Saad N. (Iraqi Journal of Science, 2022)
This study is concerned with channel banks slopes in the middle sector of Al-Massab Al-Aam channel in the middle and south of Iraq. The geotechnical properties of soil in the channel banks including physical ,engineering, chemical and mineralogical characters in over (25) station have been studied.The grain size distribution of the bank soils of channel showed that the clay percentage is higher than those of the silt and sand percentages.The bank soils are classified according to the USCS standards. They are composed of clay with low plasticity (CL) that represents 88% of the soil and ,clay with high plasticity (CH)represents 12% of the soil. The saturated density values ranges between 1.679 and 1.953 g/cm3 with average value of 1.790 g/cm3,while the dry density values ranges between 1.274 and 1.718 g/cm3 with average value of 1.470 g/cm3 ; the values of dry and saturated density are within the ideal limits . Direct shear test shows that the cohesion values (c), range between 5-48 kN/m2 with average value of 21.68 kN/m2 , while the internal friction angle (Ø°) of the soil type (CL) ranges between 8.5°-30° with average value of 18.13° . The (Ø°) values of the other soil type (CH) ranges between (20°-30°) with average value of 25° ,therefore the (CH) soil types have higher(Ø°) values than the ideal limits .The result of unconfined compression test ranges between 9.4-73.80 kN/m2 with average value of 30.6 kN/m2 of remoulded samples with water percentage of 30%.The mineralogical test of the banks soil of channel using XRD shows that the mineral contents of the analyzed soil are composed mainly of the minerals Quartz ,calcite, Feldspar (Anorthite), dolomite, and Clay minerals such as (montimorillonite, and Kaolinite) .The Electrical conductivity of soil is classified depending on (FAO) classification between low to high salinity , and the pH value have low to moderate basicity.The gypsum concentrations range between 0.09 and 12.59% with average value of 2.083% , chlorides concentrations range between 0.017 and 0.166% with average value of 0.079%, sulphates concentrations range between 0.044 and 5.85% with average value of 0.987%,and carbonates concentrations range between 2 and 40%with average value of 20.5% . Some treatment measures are proposed to stabilize the soil of the studied area.